find x, y and z
x - z = -5
2x+3y+2z=12
x+y+3z=13
x - z = -5
2x+3y+2z=12
x+y+3z=13
-
use row reductions
[1, 0, -1, -5]
[2, 3, 2, 12]
[1, 1, 3, 13]
add 2 times first row to second
[1, 0, -1, -5]
[0, 3, 4, 22]
[1, 1, 3, 13]
add -1 times first row to third
[1, 0, -1, -5]
[0, 3, 4, 22]
[0, 1, 4, 18]
multiply second row by 1/3
[1, 0, -1, -5]
[0, 1, 4/3, 22/3]
[0, 1, 4, 18]
add -1 times second row to third
[1, 0, -1, -5]
[0, 1, 4/3, 22/3]
[0, 0, 8/3, 32/3]
multiply 3rd row by 3/8
[1, 0, -1, -5]
[0, 1, 4/3, 22/3]
[0, 0, 1, 4]
add -4/3 times 3rd row to the 2nd
[1, 0, -1, -5]
[0, 1, 0,2]
[0, 0, 1, 4]
add 3rd row to 1st
[1, 0, 0, -1]
[0, 1, 0,2]
[0, 0, 1, 4]
x=-1
y=2
z=4
[1, 0, -1, -5]
[2, 3, 2, 12]
[1, 1, 3, 13]
add 2 times first row to second
[1, 0, -1, -5]
[0, 3, 4, 22]
[1, 1, 3, 13]
add -1 times first row to third
[1, 0, -1, -5]
[0, 3, 4, 22]
[0, 1, 4, 18]
multiply second row by 1/3
[1, 0, -1, -5]
[0, 1, 4/3, 22/3]
[0, 1, 4, 18]
add -1 times second row to third
[1, 0, -1, -5]
[0, 1, 4/3, 22/3]
[0, 0, 8/3, 32/3]
multiply 3rd row by 3/8
[1, 0, -1, -5]
[0, 1, 4/3, 22/3]
[0, 0, 1, 4]
add -4/3 times 3rd row to the 2nd
[1, 0, -1, -5]
[0, 1, 0,2]
[0, 0, 1, 4]
add 3rd row to 1st
[1, 0, 0, -1]
[0, 1, 0,2]
[0, 0, 1, 4]
x=-1
y=2
z=4
-
Use equation 1 to express x in terms of z by adding z to both sides:
x = z - 5
Substitute z - 5 for x in the other two equations:
2(z - 5) + 3y + 2z = 12
(z - 5) + y + 3z = 13
Simplify both equations:
1) 2z - 10 + 3y + 2z = 12
4z - 10 + 3y = 12
4z + 3y = 22
2) (z - 5) + y + 3z = 13
4z - 5 + y = 13
4z + y = 18
Subtract the second from the first:
4z + 3y = 22
-(4z + y = 18)
-----------------
2y = 4
y = 2
Substitute 2 for y and solve for z:
4z + y = 18
4z + 2 = 18
4z = 16
z = 4
Since x = z - 5:
x = 4 - 5 = -1
x = -1, y = 2, z = 4
x = z - 5
Substitute z - 5 for x in the other two equations:
2(z - 5) + 3y + 2z = 12
(z - 5) + y + 3z = 13
Simplify both equations:
1) 2z - 10 + 3y + 2z = 12
4z - 10 + 3y = 12
4z + 3y = 22
2) (z - 5) + y + 3z = 13
4z - 5 + y = 13
4z + y = 18
Subtract the second from the first:
4z + 3y = 22
-(4z + y = 18)
-----------------
2y = 4
y = 2
Substitute 2 for y and solve for z:
4z + y = 18
4z + 2 = 18
4z = 16
z = 4
Since x = z - 5:
x = 4 - 5 = -1
x = -1, y = 2, z = 4